PHYSICAL READINESS OF CHILDREN FOR SCHOOL ACTIVITIES: PHYSICAL READINESS OF CHILDREN FOR SCHOOL ACTIVITIES - Vacheva , Snezhana (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The paper dwells on the model of children’s physical readiness for school activities. It further comments on the following criteria: good health condition of the child, child’s fitness, level of endurance and industriousness of the child’s body, high level of resistance against diseases, harmonic physical and nerve-psychic development, high level of motor development, cultural-hygienic habits and manners in maintaining the principles of personal hygiene, motor skills; physical skills with children, interest and desire for participating in physical activities.